Nomenclatural changes and lectotype designations in the seed-beetle genus Sennius Bridwell: with the synonymization of Megasennius Whitehead & Kingsolver (Coleoptera: Chrysomelidae: Bruchinae) - Viana, Jéssica Herzog (Zootaxa, 2016)
Until this study, Sennius Bridwell, 1946 included 60 species. As part of an ongoing revision of this genus, nomenclatural changes, synonymies, lectotype designations and corrections of misspelled names are presented, updating to a total of 68 species for this genus. One species is transferred from Sennius Bridwell, 1946 to Acanthoscelides Schilsky 1905, megacornis group: A. infractus (Johnson & Kingsolver, 1973) comb. n.. Eight species are transferred from Acanthoscelides Schilsky 1905 to Sennius Bridwell, 1946: S. aequinoctialis (Fåhraeus, 1839) comb. n., S. amazonicus (Pic, 1929) comb. n., S. batesii (Jekel, 1855) comb. n., S. diosanus (Pic, 1930) comb. n., S. notatopygus (Pic, 1930) comb. n., S. reductus (Pic, 1930) comb. n., S. transversesignatus (Fåhraeus, 1839) comb. n. and S. ventralis (Fåhraeus, 1839) comb. n.. One species is transferred from Megasennius Whitehead & Kingsolver 1975 to Sennius: S. muricatus (Sharp, 1885) comb. n.. One variety is elevated to species rank and transferred to Sennius: Sennius rufopygus (Pic, 1934) stat. n. comb. n. from Acanthoscelides carneofasciatus v. rufopygus Pic, 1934. New synonymies are proposed: The monotypic genus Megasennius Whitehead & Kingsolver 1975 is synonymized with Sennius as its type species is transferred to Sennius. Sennius batesii (Jekel, 1855) comb. n. = Bruchus subaenescens Pic, 1931 syn. n.; Sennius bicoloripes (Pic, 1930) = Bruchus bicoloripes var. jatayensis Pic, 1930 syn. n. and Bruchus bicoloripes var. indiversipes Pic, 1930 syn. n.; Sennius subdiversicolor (Pic, 1931) = Bruchus subdiversicolor var. innigripes Pic, 1931 syn. n.; Sennius transversesignatus (Fåhraeus, 1839) comb. n. = Bruchus carneofasciatus Pic, 1927 syn. n. and Bruchus carneofasciatus var. subapicalis Pic, 1930 syn. n.; and Sennius trinotaticollis (Pic, 1930) = Bruchus diversicollis Pic, 1930 syn. n. Lectotypes are designated for B. diversicollis, B. subdiversicolor var. innigripes, Sennius aequinoctialis, S. amazonicus, S. diosanus, S. reductus, S. rufopygus and S. subdiversicolor. Correct original spellings are noted for Bruchus batesii and B. lebasii Fåhraeus, 1839 in place of the incorrect subsequent spellings of Sennius batesi and Sennius lebasi.